Implementasi Metode Contextual Teaching And Learning (CTL) untuk Meningkatkan Hasil Belajar Siswa Kelas IV pada Mata Pelajaran Pendidikan Kewarganegaraan di SDN 09 Rangkang - Intan Intan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to explore the effect of the Contextual Teaching and Learning (CTL) method on improving student learning outcomes in Civic Education subjects in grade IV of SD Negeri 09 Rangkang. The background of this study is the low student learning outcomes caused by the use of conventional learning methods that are less effective. The method used is classroom action research (CAR) with two cycles, involving 30 students as subjects. Data were collected through observation, tests, and student worksheets. The results showed that the application of the CTL method can significantly increase student active participation and their learning outcomes. The average student score increased from 70 in cycle I to 85 in cycle II. In conclusion, the CTL method is effective in improving student learning outcomes and can be a good alternative for teachers in teaching complex materials. This study recommends that teachers apply the CTL method consistently to improve the quality of learning in the classroom. Thus, the CTL method can be a practical solution to the problem of low learning outcomes in elementary schools and help create a more interesting and interactive learning environment for students.